Factors Affecting the Incidence of Early Age Marriage of Adolescent Girls at Lembah Melintang Subdistrict Pasaman Barat District - Narti, Samsi; Siagian, Mindo Tua; Etty, Christina Roos (Sari Mutiara Indonesia University Press, 2018)
Early marriage is a wedlock done by someone who is under <20 years old. Its impact on a pregnant and childbirth woman is material mortality 2 to 5 times higher than those who are 20 to 29 years old, while its social impact is that it can cause a divorce. It can also cause anemia, BBLR (low weight born baby), abortion, and have double risk for cervical cancer. The objective of the research was to analyze some factors which influenced the incidence of early marriage in Lembah Melintang subdistrict, PasamanBarat Regency. The research analytic observational method with case control design. The samples were 96 respondents with inclusion and exclusion criteria. The data were analyzed by using univariate analysis, bivariate analysis with chi-square test and multivariate test with logistic regression test. The results of the showed that early were significantly influenced by knowledge, attitude, culture and parents’ care pattern. The results of logistic regression analysis showed that the factors which had dominant influence on the incidence of early marriage were knowledge at OR=9,061parents’ care pattern at OR=11,043, and culture at OR=12,230. It is recommended that health care providers, especially midwives and personnel at the Residential Affairs Office activate PIKR (Teenager Counseling adan Information Center) program and BKR (Adolescents’ Family Fostering), Cooperation of Inter-Program and Inter-Sectoral such as BKKBN, the Health Agency, religious figures, public figures, school principals, and KUA Head, if possible.